RETRACTED: The Performance of the Fire Service Office of Central Bengkulu Regency in Dealing with Fire Hazards - Risondi, Risondi; Lorita, Evi; Imanda, Antonio (Social Sciences Journal, 2024)
Following up on the review of articles published in the Social Sciences Journal carefully, carefully, and considering the article entitled "The Performance of the Fire Service Office of Central Bengkulu Regency in Dealing with Fire Hazards" Vol 1 No 1 (2024). This paper was found to violate the Social Sciences Journal Publication principles and has been withdrawn.This article has been published in the journal ISO.The document and its contents have been removed from the Social Sciences Journal, and reasonable efforts should be made to remove all references to this article.